A Multi-Criteria Decision Approach to Livability Assessment Using Hybrid FUCOM–VIKOR - Maharani, Felina Devi; Cholil, Saifur Rohman (Politeknik Negeri Batam, 2026)
Persistent disparities in regional livability across Central Java pose challenges for effective and equitable poverty alleviation policies. Without objective prioritization, government interventions risk being inefficient and misdirected. This study aims to assess the livability level of 35 regencies and cities in Central Java and to identify regions that should be prioritized for policy intervention. Secondary data for 2024 were obtained from the Central Statistics Agency (BPS) of Central Java Province. A hybrid multi-criteria decision-making approach combining the Full Consistency Method (FUCOM) and VIKOR was employed. FUCOM was used to generate consistent and objective weights for six indicators (Human Development Index, Life Expectancy, Number of Poor Residents, Open Unemployment Rate, Access to Proper Sanitation, and GRDP per capita), while VIKOR was applied to produce compromise-based rankings of regional livability. The ranking results were visualized using a bar chart to enhance interpretability and facilitate regional comparison. The results indicate that Salatiga City, Magelang City, and Surakarta City exhibit the highest livability levels, whereas Brebes Regency, Banjarnegara Regency, and Pemalang Regency consistently rank lowest, indicating an urgent need for targeted government intervention. Model validation using Normalized Discounted Cumulative Gain (NDCG = 0.9835) and Spearman Rank Correlation (ρ = 0.883) demonstrates strong consistency with reference data. These findings suggest that the FUCOM–VIKOR hybrid approach provides a robust and practical decision-support tool for evidence-based regional development planning and poverty alleviation prioritization.